2016
DOI: 10.3928/01477447-20151222-07
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Risk of Swallowing-Related Pulmonary Complications in Older Patients With Hip Fracture

Abstract: To identify and potentially modify the risk of pulmonary complications in a group of older patients with hip fracture, the authors obtained speech and language pathology consultations for these patients. Then they performed a retrospective chart review of all patients 65 years and older who were admitted to their institution between June 2011 and July 2013 with acute hip fracture, were treated surgically, and had a speech and language pathology evaluation in the immediate perioperative period. The authors iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
1
14
4
Order By: Relevance
“…Recently, Belmont Jr et al reported that pneumonia was diagnosed in just 4.6% of hip fracture patients, which is much lower than the percentage reported in the current study . This discrepancy might be attributed to the fact that the patients included in the present study and in that by Roche et al are older than those included in the study by Belmont Jr et al Dysphagia and aspiration pneumonia are more common among frail older patients owing to their impaired swallowing function . Furthermore, age has been reported as a risk factor of postoperative complications and mortality in hip fracture patients .…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Recently, Belmont Jr et al reported that pneumonia was diagnosed in just 4.6% of hip fracture patients, which is much lower than the percentage reported in the current study . This discrepancy might be attributed to the fact that the patients included in the present study and in that by Roche et al are older than those included in the study by Belmont Jr et al Dysphagia and aspiration pneumonia are more common among frail older patients owing to their impaired swallowing function . Furthermore, age has been reported as a risk factor of postoperative complications and mortality in hip fracture patients .…”
Section: Discussioncontrasting
confidence: 71%
“…10 This discrepancy might be attributed to the fact that the patients included in the present study and in that by Roche et al 9 are older than those included in the study by Belmont Jr et al 10 Dysphagia and aspiration pneumonia are more common among frail older patients owing to their impaired swallowing function. 16,18,22 Furthermore, age has been reported as a risk factor of postoperative complications and mortality in hip fracture patients. 9,20 In corroboration with these findings, age was identified as an independent risk factor of aspiration pneumonia after regression analysis in the present study as well.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects' physical condition before surgery was assessed by ASA scores (American Society of Anesthesiologists) [14,22]. The ASA physical status classifies the patients' fitness before surgery into 6 classes: (1) normal health, (2) mild systemic disease, (3) severe systemic disease, (4) severe life-threatening systemic disease, (5) a moribund patient, or (6) a brain-dead organ donor.…”
Section: Baseline Parametersmentioning
confidence: 99%
“…Cases of sarcopenia were reported in 17~58% of older patients with hip fractures [11][12][13]. Furthermore, dysphagia was reported to occur in 5.3~44% of patients who underwent operative treatment for hip fractures [14][15][16][17]. Dysphagia in older patients with hip fracture was associated with risk factors such as low serum albumin levels, female gender, confusion after surgery, and preoperative worsening of physical status [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation